Time Domain Analysis of Ultra-Wide Band Signals from Buried Objects Under Flat and Slightly Rough Surfaces - MakalYucedag, S.; Kizilay, A. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The analysis of transient scattering for TMz (horizontally) polarization from a cylindrical perfectly conducting (PEC) object buried in a lossy medium is considered. Flat and slightly surface cases are considered for the dielectric halfspace. Our previous work using a decomposition method solution in frequency domain of TMz polarization is utilized to solve this scattering problem. Then, an inverse Fourier transform is used to get the time domain signals. Timing analysis is done by calculating the travelling time of reflected signals in the possible paths. Then, multiple reflections are identified using these travelling times. Finally, the results from the flat and slightly rough surface profiles are used to compare the effects of multipath propagation.